9x+17-3x=12+4x+5

Simple and best practice solution for 9x+17-3x=12+4x+5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9x+17-3x=12+4x+5 equation:


Simplifying
9x + 17 + -3x = 12 + 4x + 5

Reorder the terms:
17 + 9x + -3x = 12 + 4x + 5

Combine like terms: 9x + -3x = 6x
17 + 6x = 12 + 4x + 5

Reorder the terms:
17 + 6x = 12 + 5 + 4x

Combine like terms: 12 + 5 = 17
17 + 6x = 17 + 4x

Add '-17' to each side of the equation.
17 + -17 + 6x = 17 + -17 + 4x

Combine like terms: 17 + -17 = 0
0 + 6x = 17 + -17 + 4x
6x = 17 + -17 + 4x

Combine like terms: 17 + -17 = 0
6x = 0 + 4x
6x = 4x

Solving
6x = 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
6x + -4x = 4x + -4x

Combine like terms: 6x + -4x = 2x
2x = 4x + -4x

Combine like terms: 4x + -4x = 0
2x = 0

Divide each side by '2'.
x = 0

Simplifying
x = 0

See similar equations:

| -(3x+8)=-10 | | 6x+7-2x+4=4(9-3x-5)-17 | | -3r+9=-4r+6 | | Y/4=x-50 | | (x^2)/(3)-5=7 | | 54*12*5= | | 6(4-3x)-5+4x=13 | | 4=p1-5/40 | | 5(3p+2)-(10p-4)= | | 2(8q-5)=48 | | -2(x-7)=-4 | | 6(9x+2)-4=10x+11 | | -8-5c=64+3c | | .5mv^2=k | | x=yz/6 | | -8-5c=644 | | 29*10*31= | | -58=y-16 | | x+1(x+13)=85 | | 2(3x+4)-5=7-x | | 8x+7+12x=-5x-43 | | 5x-.20=.80 | | 6y^2=7y-2 | | x^3-49x-686=0 | | 10=.5mv^2 | | 8r+6+4r-1=14 | | 8-(2*x)=x+17 | | 20v^2-41vt+20t^2=0 | | 10=3(x-1)-(x-7) | | x+24-9x=-80 | | 4x=81/16 | | 36/x=12 |

Equations solver categories